Meaning and philosophy of Bale beleq traditional house East Lombok - Septiana, Elmi; Afandi, Ahmad; Ilmiawan, Ilmiawan; Herianto, Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
The Bale beleq traditional house of Jerowaru Village and Wakan Village is a historical heritage. This house is different from ordinary traditional houses because Bale beleq is occupied by people who are respected. In addition, there are also historical relics such as keris, swords, and many more. This research aims to examine information about the meaning and philosophy of the Bale beleq traditional house. This research was conducted in Jerowaru Village and Wakan Village. Eight respondents were interviewed. The research method used was the qualitative method. Data collection was done by using observation, interview, and documentation methods. The data analysis techniques are data collection, data reduction, data presentation, and conclusion drawing or verification. The results of the study found the history of the emergence of the Bale beleq traditional house, the meaning and philosophy of Bale beleq, and the values within Bale beleq. Currently, Bale beleq is used as a center for socio-cultural religious activities. One way to maintain and preserve traditional houses is to make the house a cultural heritage so that it does not erode with the time, and to make Bale beleq an educational and cultural tour site.